Analysis of the South China SEA: Resource Potential and Future Conflict Risks for Asean Countries - Yunanto, Ari (Green Publisher Indonesia, 2025)
The South China Sea represents one of the most strategically significant maritime regions globally, characterized by complex territorial disputes involving China, Taiwan, Philippines, Vietnam, Malaysia, and Brunei. This study examines the resource potential of the South China Sea and analyzes how these resources influence conflict risks for ASEAN member states. Employing qualitative research methodology through case study design and process-tracing techniques, this research investigates the interplay between natural resource exploitation, territorial claims, and security dynamics in the region. The findings reveal that the South China Sea contains substantial reserves of oil (estimated 11 billion barrels), natural gas (190 trillion cubic feet), and fisheries resources (8 million metric tons annually), alongside serving as a critical international trade route with approximately 5.3 trillion in goods transiting annually. The territorial disputes are exacerbated by competing interpretations of the United Nations Convention on the Law of the Sea (UNCLOS), China's nine-dash line claims, and increasing militarization of disputed features. ASEAN's mediation efforts face significant challenges due to diverse member interests, Chinese economic leverage, and external power involvement. The study concludes that effective conflict management requires strengthened ASEAN unity, enhanced diplomatic mechanisms, adherence to international law, and cooperative frameworks for resource sharing. The research contributes to understanding how resource-rich maritime territories shape regional security architecture and provides policy recommendations for peaceful dispute resolution in contested waters.